Improving hospital hygiene to reduce the impact of multidrug-resistant organisms in health care–a prospective controlled multicenter study. Issue 1 (December 2015) - Gerlich, Miriam; Piegsa, Jens; Schäfer, Christian; Hübner, Nils-Olaf; Wilke, Florian; Reuter, Susanne; Engel, Georg; Ewert, Ralf; Claus, Franziska; Hübner, Claudia; Ried, Walter; Flessa, Steffen; et al.
Abstract Background Nosocomial infections are the most common complication during inpatient hospital care. An increasing proportion of these infections are caused by multidrug-resistant organisms (MDROs). This report describes an intervention study which was designed to address the practical problems encountered in trying to avoid and treat infections caused by MDROs. The aim of the HARMONIC (Harmonized Approach to avert Multidrug-resistant Organisms and Nosocomial Infections) study is to provide comprehensive support to hospitals in a defined study area in north-east Germany, to meet statutory requirements. To this end, a multimodal system of hygiene management was implemented in the participating hospitals. Methods/design HARMONIC is a controlled intervention study conducted in eight acute care hospitals in the 'Health Region Baltic Sea Coast' in Germany. The intervention measures include the provision of written recommendations on methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococci (VRE) and multi-resistant Gram-negative bacteria (MRGN), supplemented by regional recommendations for antibiotic prescriptions. In addition, there is theoretical and practical training of health care workers (HCWs) in the prevention and handling of MDROs, as well as targeted and critically gauged applications of antibiotics. The main outcomes of the implementation and analysis of the HARMONIC study are: (i) screening rates for MRSA, VRE and MRGN in high-risk patients, (ii) the frequency of MRSA decolonization, (iii) the level of knowledge of HCWs concerning MDROs, and (iv) specific types and amounts of antibiotics used. The data are predominantly obtained by paper-based questionnaires and documentation sheets. A computer-assisted workflow-based documentation system was developed in order to provide support to the participating facilities. The investigation includes three nested studies on risk profiles of MDROs, health-related quality of life, and cost analysis. A six-month follow-up study investigates the quality of life after discharge, the long-term costs of the treatment of infections caused by MDROs, and the sustainability of MRSA eradication. Discussion The aim of this study is to implement and evaluate an area-wide harmonized hygiene program to control the nosocomial spreading of MDROs. Comparability between the intervention and control group is ensured by matching the hospitals according to size (number of discharges per year / number of beds) and level of care (standard or maximum). The results of the study may provide important indications for the implementation of regional MDRO management programs.